On the effect of wax content on paraffin wax deposition in a batch oscillatory baffled tube apparatus - Ismail, Lukman; Westacott, Robin E.; Ni, Xiongwei (Elsevier, 2008)
Deposition of paraffin wax is one of the major problems facing in the petroleum industries with the main implication being wax blockage in oil and gas pipelines especially for offshore production. The objectives of this work are to investigate the effect of applying oscillatory motion on wax deposition in an oscillatory baffled tube apparatus, a relatively new mixing technology that offers more uniform mixing and solid suspension than traditional devices; and are to understand the mechanism and kinetics of the wax crystallisation in accordance to the Avrami theory. The wax deposition was determined gravimetrically. The results indicate that the oscillatory motion has two opposite effects on the percentage of wax deposition: at low concentration of wax in solution, the presence of oscillation significantly reduces the wax deposition, e.g. 40–60% without the presence of any solvent or wax inhibitor; and completely prevents 100% wax gelation from occurring – the beneficial effect; at higher wax contents, however, the introduction of oscillatory motion not only promotes wax deposition, but also accelerates the crystal growth to achieve 100% wax deposition – the detrimental effect.